Sharing and giving across adolescence: an experimental study examining the development of prosocial behavior - Güroğlu, Berna; van den Bos, Wouter; Crone, Eveline A. (Frontiers in Psychology, 2014)
In this study we use economic exchange games to examine the development of prosocial behavior in the form of sharing and giving in social interactions with peers across adolescence. Participants from four age groups (9-, 12-, 15-, and 18-year-olds, total N = 119) played three types of distribution games and the Trust game with four different interaction partners: friends, antagonists, neutral classmates, and anonymous peers. Nine- and 12-year-olds showed similar levels of prosocial behavior to all interaction partners, whereas older adolescents showed increasing differentiation in prosocial behavior depending on the relation with peers, with most prosocial behavior toward friends. The age related increase in non-costly prosocial behavior toward friends was mediated by self-reported perspective-taking skills. Current findings extend existing evidence on the developmental patterns of fairness considerations from childhood into late adolescence. Together, we show that adolescents are increasingly better at incorporating social context into decision-making. Our findings further highlight the role of friendships as a significant social context for the development of prosocial behavior in early adolescence.